Use of PCR technique for direct detection of Brucella spp. from milk of sheep and cattle: Haifaa Jimaa Al-Hasnawi; Basima Jassim Al-Gurabi and Hassan Hachim Naser - Naser, Hassan Hachim (The Iraqi Journal of Veterinary Medicine, 2014)
Brucella spp are important food pathogen those can be infected the human-being during consumption of contaminated milk and milk products from sheep, goats, and cattle with Brucella spp. In this study the polymerase chain reaction (PCR) for direct detection of Brucella spp. from milk of sheep and cattle were employed to amplify 233bp product of highly conserved regions of BCSP31 gene encoding a 31-KDa cell surface protein in B. melitensis and B. abortus. The results showed that the sheep were more frequent for shedding of Brucella spp in their milk, where appeared (6/50 samples) at (12%). Whereas the cattle appeared less frequency for shedding of Brucella in their milk, which showed (2/50 samples) at (4%). It can be concluded that PCR technique is highly sensitive and specific technique for direct detection of Brucella from milk and the sheep and cattle can be shedding the Brucella in their milk. Therefore, the contaminated milk with Brucella spp may have dangerous effect on public health, when consumed by human